Bartonella henselae Bloodstream Infection in a Boy With Pediatric Acute-Onset Neuropsychiatric Syndrome. (March 2019) - Breitschwerdt, Edward B; Greenberg, Rosalie; Maggi, Ricardo G; Mozayeni, B Robert; Lewis, Allen; Bradley, Julie M
Background: With the advent of more sensitive culture and molecular diagnostic testing modalities, Bartonella spp. infections have been documented in blood and/or cerebrospinal fluid specimens from patients with diverse neurological symptoms. Pediatric acute-onset neuropsychiatric syndrome (PANS) is characterized by an unusually abrupt onset of cognitive, behavioral, or neurological symptoms. Between October 2015 and January 2017, a 14-year-old boy underwent evaluation by multiple specialists for sudden-onset psychotic behavior (hallucinations, delusions, suicidal and homicidal ideation). Methods: In March 2017, Bartonella spp. serology (indirect fluorescent antibody assays) and polymerase chain reaction (PCR) amplification, DNA sequencing, and Bartonella enrichment blood culture were used on a research basis to assess Bartonella spp. exposure and bloodstream infection, respectively. PCR assays targeting other vector-borne infections were performed to assess potential co-infections. Results: For 18 months, the boy remained psychotic despite 4 hospitalizations, therapeutic trials involving multiple psychiatric medication combinations, and immunosuppressive treatment for autoimmune encephalitis. Neurobartonellosis was diagnosed after cutaneous lesions developed. Subsequently, despite nearly 2 consecutive months of doxycycline administration, Bartonella henselae DNA was PCR amplified and sequenced from the patient's blood, and from Bartonella alphaproteobacteria growth medium enrichment blood cultures. B henselae serology was negative. During treatment with combination antimicrobial chemotherapy, he experienced a gradual progressive decrease in neuropsychiatric symptoms, cessation of psychiatric drugs, resolution of Bartonella -associated cutaneous lesions, and a return to all pre-illness activities. Conclusions: This case report suggests that B henselae bloodstream infection may contribute to progressive, recalcitrant neuropsychiatric symptoms consistent with PANS in a subset of patients.